PERANAN PEMBINAAN DAN PENGAWASAN PADA PENGUSAHAAN AIR TANAH DI UPT DINAS ESDM PROVINSI JAWA BARAT WILAYAH PELAYANAN I CIANJUR - Setiawan, Wawan; Iskandar, Abubakar; Pratidina, Ginung (Fakultas Ilmu Sosial Ilmu Politik Universitas Djuanda Bogor, 2018)
This study aims to determine the role of guidance and supervision in groundwater exploitation in the Technical Implementation Unit of the Department of Energy and Mineral Resources (UPTDESDM) West Java Province Service Area I Cianjur. With working areas including: Cianjur, Sukabumi, Sukabumi, Bogor, Bogor and Depok.According to Pratowo (2001) the success of groundwater management is highly dependent on supervisory and control functions, including coaching function. Ivancevich put forward a number of important points, namely, coaching is a systematic process to change the work behavior of a / group of employees in an effort to improve organizational performance. Georgr R.Terry (2006: 395) defines oversight as disseminating what has been done.Â That is to evaluate work performance and if necessary apply corrective action action so that the result of work according to the plan has been determined. Business is the process, the way, the act of cultivating and organizing. Groundwater or so-called ground water is-water located beneath the soil surface in the zone or water-saturated layer. Methodology This research uses descriptive research design with qualitative approach method. The analyst unit in this research is in the form of individual / informant. The research informants were chosen by purposive sampling, while the technique technique used in this research are: Observation, Interview, and Documentation. Results and discussion: 1. Checking / analysis of groundwater quality, 2. Groundwater retrieval data, 3. Ground water tax, 4. Technological consideration of groundwater extraction permitSuggestion writer for Office of UPT Department of ESDM West Java Province Service Area I Cianjur must continue to run coaching and supervision for the preservation of water resources, especially ground water remain awake and sustainable.Â Keywords: Guidance, Monitoring and Operation of ground water